Differential Behavior of Fibroblasts and Epithelial Cells on Structured Implant Abutment Materials: A Comparison of Materials and Surface Topographies. (26th July 2014) - Nothdurft, Frank P.; Fontana, Dorothee; Ruppenthal, Sandra; May, Alexander; Aktas, Cenk; Mehraein, Yasmin; Lipp, Peter; Kaestner, Lars
Abstract: Purpose: The aim of this study was to compare the proliferation and attachment behavior of fibroblasts and epithelial cells on differently structured abutment materials. Materials and Methods: Three different surface topographies were prepared on zirconia and titanium alloy specimens and defined as follows: machined (as delivered without further surface modification), smooth (polished), and rough (sandblasted). Energy‐dispersive X‐ray spectroscopy, topographical analysis, and water contact angle measurements were used to analyze the surface properties. Fibroblasts (HGF1) and epithelial cells (HNEpC) grown on the specimens were investigated 24 hours and 72 hours after seeding and counted using fluorescence imaging. To investigate adhesion, the abundance and arrangement of the focal adhesion protein vinculin were evaluated by immunocytochemistry. Results: Similar surface topographies were created on both materials. Fibroblasts exhibited significant higher proliferation rates on comparable surface topographies of zirconia compared with the titanium alloy. The proliferation of fibroblasts and epithelial cells was optimal on different substrate/topography combinations. Cell spreading was generally higher on polished and machined surfaces than on sandblasted surfaces. Rough surfaces provided favorable properties in terms of cellular adhesion of fibroblasts but not of epithelial cells. Conclusions: Our data support complex soft tissue cell‐substrate interactions: the fibroblast and epithelial cell response is influenced by both the material and surface topography.